Dynamics of the Development of the Middle Eastern Education System and Its Implementation in Indonesia Facing the Era of Society 5.0 - Muslim, Afifi Marzuki; Nurwahidin; Mulawarman Hannase; Amany Burhanuddin Umar Lubis (CV. Era Digital Nusantara, 2024)
Middle Eastern and Islamic civilizations are very complex civilizations, from the classical to the modern period. The dynamics of education in the portrait of Middle Eastern and Islamic civilizations are also very diverse. Its influence has had a tremendous impact on regional and even global civilizations. In the midst of the rapid and massive development of the world. Even though society has not finished adjusting to the Industrial Revolution 4.0, Japan introduced the idea of ​​society 5.0. This is in accordance with the objectives of the SDGs which are being achieved in a global context including the field of education. However, Indonesia still has a lot of work to be done in the education system in Indonesia. So it is hoped that through this article researchers can see the relevance of the development of the world of education with the idea of ​​society 5.0 in Indonesia along with its implementation.